Fatigue Strength of Rotary Bending Copper Materials - N Talango; S Ishak; NS Dera; W Rauf (BIOMEJ, 2023)
Non-ferrous metal is a type of metal that does not contain iron (Fe). Pure non-ferrous metals do not need alloying elements because of their chemical resistance and good electrical conductivity. The non-ferrous metal in question is copper. Almost every human need can’t be separated from the element of copper as a supporting material. In the industrial world, copper has an important role because many factory machinery construction utilizes this material. Copper is a material that conducts heat and electricity quite well and has smooth and soft properties. The durability of copper-based structures can be carried out by fatigue tests (fatigue). This study aims to analyze the fatigue strength of copper material with rotary bending type. The test was carried out on copper material without heat treatment. At each loading, the test was carried out five times on different test specimens (Sp1, Sp2, Sp3, Sp4, and Sp5) with variations in the load determined at 15 kg, 17 kg, and 19 kg. Preparation of test specimens using a lathe and photos of micro and macro structures using a microscope. While the fatigue test was carried out using a rotary bending type fatigue test machine. The results of microstructure observations for all loadings showed that the specimens had soft properties. Meanwhile, the observation of the macro structure shows that the specimen has brittle properties. The results of the fatigue test show that the flexural stresses for each load of 15 kg, 17, kg, and 19 kg are written as 33 kg/mm2, 37 kg/mm2, and 42 kg/mm2, respectively.